Characterization of the Th cytokines profile in ovine spleen during early pregnancy. Issue 1 (1st January 2019) - Li, Ning; Zhao, Zimo; Bai, Jiachen; Liu, Baoliang; Mi, Hao; Zhang, Leying; Li, Guiping; Yang, Ling
ABSTRACT: The spleen combines the innate and adaptive immune systems, and the early conceptus must regulate the maternal intrauterine immune and systemic immune response during early pregnancy in sheep. However, it is unclear whether early pregnancy exerts its effects on the characterization of the T helper (Th) cytokines profile in the spleen during early pregnancy in ewes. In this study, spleens were obtained at day 16 of the oestrous cycle and at days 13, 16 and 25 of pregnancy ( n = 6 for each group) from ewes, and qRT-PCR, western blot and immunohistochemistry analysis were used to analyze the Th cytokines profile of the spleens. Our results showed that there was down-regulation of IFN-γ at days 13 and 16 of pregnancy, but there was upregulation of IL-2, IL-5 and IL-6 at day 25 of pregnancy, TNF-β at days 16 and 25 of pregnancy, and IL-4 and IL-10 in all pregnant groups. Immunohistochemistry results showed that the IL-6 protein was limited to the capsule, trabeculae and splenic cords. This paper reported, for the first time, that characterization of the Th cytokines profile varied in the maternal spleen during early pregnancy, which may be essential for successful pregnancy in sheep.